DAMPAK PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA BIDANG SENI RUPA - SRI RAHMI, Drs. Abd. Hafiz, M.Pd, Dra.Zubaidah, M.Pd (Universitas Negeri Padang, 2015)
This study aims to determine the impact of the learning model ofthe Discovery Learning the learning outcomes of arts and culture in thefield of visual arts class VII SMP Negeri 35 Padang . This research isexperimental research with quantitative methods approach . Classes areselected as the sample is VII.5 class as experimental class and the class asa class VII.2 control . Data collection techniques in this research is toprovide test results to learn , while the data collection tool is theachievement test . The data analysis technique used in this study is tocompare the difference of the two average values , so done to test thehypothesis that t = 4.78 > table = 1.98 .Kata kunci: hasil belajar, mata seni rupa, Discovery Learning.